2016
DOI: 10.1111/ene.13078
|View full text |Cite
|
Sign up to set email alerts
|

Impulse control disorder related behaviours during long‐term rotigotine treatment: a post hoc analysis

Abstract: Background and purposeDopamine agonists in Parkinson's disease (PD) are associated with impulse control disorders (ICDs) and other compulsive behaviours (together called ICD behaviours). The frequency of ICD behaviours reported as adverse events (AEs) in long‐term studies of rotigotine transdermal patch in PD was evaluated.MethodsThis was a post hoc analysis of six open‐label extension studies up to 6 years in duration. Analyses included patients treated with rotigotine for at least 6 months and administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 31 publications
0
49
0
2
Order By: Relevance
“…For example, a prospective cohort study reported a median time of 23.0 months after DA initiation to ICD onset 27. In a recent ‘post hoc’ analysis of ICD behaviours reported as adverse events in long-term studies of DA rotigotine, the number of incident cases during the first 30 months was relatively low and increased afterwards, suggesting a lag time to ICD onset in many patients 41. Furthermore, medication doses were not recorded in this non-interventional study, and thus it was not possible to calculate the levodopa equivalent daily dose (LEDD) for each PD therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a prospective cohort study reported a median time of 23.0 months after DA initiation to ICD onset 27. In a recent ‘post hoc’ analysis of ICD behaviours reported as adverse events in long-term studies of DA rotigotine, the number of incident cases during the first 30 months was relatively low and increased afterwards, suggesting a lag time to ICD onset in many patients 41. Furthermore, medication doses were not recorded in this non-interventional study, and thus it was not possible to calculate the levodopa equivalent daily dose (LEDD) for each PD therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…Although rotigotine has been reported to confer a lower risk compared with other DAs (Garcia‐Ruiz et al., 2014; Moore, Khalaj, et al., 2014; Rizos et al., 2016), rotigotine has D3 receptor affinity, and furthermore, in a post hoc analysis of six open‐label extension studies, 71 of 786 patients (9%) with rotigotine treatment developed ICB (Antonini et al., 2016). Hence, rotigotine could be a risk factor for the development of ICB.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the impact of the introduction of dopaminergic medication broadly in de novo patients, 17% of patients starting medication reported incident ICD symptoms during a 2‐year period, with no untreated patients reporting new symptoms . Looking at DAs specifically, 39% of DA‐treated patients without an ICD at baseline developed an ICD during a 4‐year period in one study, and in another study of one DA (rotigotine patch) the cumulative ICD prevalence was 9%, with median time to onset occurring 4 to 5 years after DA initiation, indicating a significant lag time …”
Section: Fundamental Epidemiological Researchmentioning
confidence: 99%